2018
DOI: 10.1016/j.redox.2018.05.012
|View full text |Cite
|
Sign up to set email alerts
|

Cyanidin and delphinidin modulate inflammation and altered redox signaling improving insulin resistance in high fat-fed mice

Abstract: Consumption of diets high in fat and/or fructose content promotes tissue inflammation, oxidative stress, and insulin resistance, activating signals (e.g. NF-κB/JNK) that downregulate the insulin cascade. Current evidence supports the concept that select flavonoids can mitigate obesity and type 2 diabetes (T2D). This work investigated if supplementation with the anthocyanidins (AC) cyanidin and delphinidin could attenuate the adverse consequences of consuming a high fat diet (HFD) in mice. Consumption of an AC-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
99
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(107 citation statements)
references
References 46 publications
4
99
0
4
Order By: Relevance
“…Despite this reduction, the energy intake remained similar among groups due to the increase in the proportion of calories from fat in the HFHC diet, as well as the energy from the drinking water. In line with our results, other studies reported similar dietetic patterns, as well as their effect on body weight [ 37 , 38 , 39 ]. C57BL/6J mice on an HFD for 15 weeks gained weight in a comparable way (~44 g of body weight) to that observed herein despite food consumption being lower, and the energy intake was not significantly different compared to those fed with a low-fat diet [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…Despite this reduction, the energy intake remained similar among groups due to the increase in the proportion of calories from fat in the HFHC diet, as well as the energy from the drinking water. In line with our results, other studies reported similar dietetic patterns, as well as their effect on body weight [ 37 , 38 , 39 ]. C57BL/6J mice on an HFD for 15 weeks gained weight in a comparable way (~44 g of body weight) to that observed herein despite food consumption being lower, and the energy intake was not significantly different compared to those fed with a low-fat diet [ 38 ].…”
Section: Discussionsupporting
confidence: 93%
“…However, studies have demonstrated the positive impact dietary anthocyanins have on microbiota in obese populations which then leads to obesity control, including decreased insulin resistance, decreased inflammation, and decreased fat storage [ 10 ]. Additionally, previous work from our group has demonstrated that a similar anthocyanin blend used in the current clinical study modulated inflammation and improved insulin resistance in high-fat-fed mice [ 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Many evidences support a potential beneficial action of polyphenols consumption on cardiovascular health [100] and type 2 diabetes mellitus [101,102]. In mice fed a high-fat diet, Daveri et al [103] have shown that polyphenols modulate inflammation and alter redox signaling, improving insulin resistance. Several studies in vivo on tea polyphenols, and especially EGCG, via dampening of PTP1B (protein tyrosine phosphatase 1B) and other PTPs acting as key regulators of tyrosine phosphorylation-dependent signaling accelerate glucose uptake and evoke the IRS-1/Akt/GLUT2 signaling pathway in HepG2 cells and mice liver [104].…”
Section: Several Other Effects Of Polyphenols/h 2 O 2 In Animal and Hmentioning
confidence: 99%
“…Circulating levels of glucose and free fatty acids are increased in patients with type 2 diabetes mellitus (T2DM) and metabolic syndrome [88,[101][102][103][115][116][117]. These effectors activate the generation of ROS, activation of NF-kB (nuclear factor kappa B) and the pro-inflammatory pathway through phosphatase and NADPH oxidases (NOX1 or NOX4) [96,118,119].…”
Section: Several Other Effects Of Polyphenols/h 2 O 2 In Animal and Hmentioning
confidence: 99%